Analisis Trend Penelitian Model Guided Inquiry untuk Meningkatkan Penalaran Ilmiah Siswa; Systematic Literature Review - Alfira Eka Putri; Kusnadi .; Mimin Nurjhani Kusumastuti (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
This study aims to analyze trends in the implementation of the Guided Inquiry model in improving students’ scientific reasoning skills. The study employed a Systematic Literature Review approach by examining 20 articles published between 2020 and 2025. The screening and eligibility processes were conducted to ensure the relevance, quality, and alignment of the selected articles with the research focus. The findings indicate that Guided Inquiry is consistently effective in enhancing students’ scientific reasoning skills at both junior and senior high school levels, particularly when combined with the Contextual Teaching and Learning (CTL) approach. The most frequently used research method was a quasi-experimental design with pre-test and post-test, allowing for empirical assessment of changes in students’ reasoning abilities. Bibliometric analysis further revealed that although the primary focus of this review is scientific reasoning, the most dominant keyword in the publications was critical thinking skills, indicating that measurements of critical thinking are more commonly conducted than those of scientific reasoning.